FCS and ECH dependent production of phenolic aldehyde and melanin pigment from L-tyrosine in Escherichia coli - Jang, Seyoung; Gang, Haemin; Kim, Byung Gee; Choi, Kwon Young (Enzyme and Microbial Technology, 2018)
In this study, we engineered E. coli cells to express L-tyrosine converting enzymes, including tyrosine ammonia-lyase (TAL), p-coumarate 3-hydroxylase (C3H), feruloyl-CoA synthetase (FCS), and enoyl-CoA hydratase/aldolase (ECH). A catabolic circuit, which consisted of the protocatechualdehyde and p-hydroxybenzaldehyde production pathways, was reconstituted through combinatorial production of discrete enzymes. First, cells expressing FCS and ECH could convert each 5 mM of caffeic acid and ferulic acid into protocatechualdehyde (70.5%) and vanillin (96.5%), respectively. Second, TAL and C3H were co-expressed with FCS and ECH. This strain converted L-tyrosine into caffeic acid, which was then converted into protocatechualdehyde. Ascorbic acid was used as an inhibitor of catechol aldehyde-based melanin formation, and the production yields of protocatechualdehyde and p-hydroxybenzaldehyde were 31.0 ± 5.6 and 24.0 ± 4.2 mg/L, respectively. Finally, caffeic acid-based melanin formation was observed with higher production rate of 40.9 ± 6.2 mg/L/h by co-expressing FCS and ECH in the presence of caffeic acid.
Keywords: Caffeic acids; Converting enzyme; l-Tyrosine; p-Hydroxybenzaldehyde; Production pathways; Production rates; Protocatechualdehyde; Tyrosine ammonia lyase; Ammonia-Lyases; Bacterial Proteins; Benzaldehydes; Burkholderia; Coenzyme A Ligases; Enoyl-CoA Hydratase; Escherichia coli; Kinetics; Melanins; Metabolic Engineering; Metabolic Networks and Pathways; Recombinant Proteins; Trans-Cinnamate 4-Monooxygenase; Tyrosine; Caffeic acid; L-tyrosine; Melanin; p-Hydroxybenzaldehyde; Protocatechualdehyde